Impact of multidisciplinary care of diabetic foot infections for inpatients at Campbelltown Hospital - Timothy Choi; Uchechukwu Levi Osuagwu; Chau Tran; Krupali Bulsari; David Simmons (BMC, 2023)
Abstract Background Diabetic foot infection (DFI), including diabetic foot ulcer, is a serious complication of diabetes, particularly in the South Western Sydney (SWS) region where it is a leading cause of diabetes-related hospitalisations. Multidisciplinary team (MDT) involvement is effective at improving the health outcomes of DFI patients. This study investigated the impact of MDT (High Risk Foot Service, HRFS) on the length of stay and surgical outcomes of inpatients with DFI in a Sydney tertiary hospital. Method A retrospective audit of electronic medical records of inpatient admissions for DFI at Campbelltown Hospital between January 2019 - December 2021, was performed. The main outcome of the study was MDT involvement, defined as having two or more specialities involved in the patient's treatment. The other measured variables included length of stay (defined as the total duration from admission to discharge), and surgical outcomes including debridement, minor amputation, and major amputation. Results Over the three years, 78 participants presented to the hospital for 89 unique DFI admissions. There were 24 admissions in 2019, 28 admissions in 2020, and 37 admissions in 2021, with MDT attendance showing a steady increase at 62.5%, 75.0% and 83.8% respectively. Patients with serious comorbidities such as chronic kidney disease were more likely to have MDT involvement (84.8% vs. 15.2%, P = 0.048). Imaging was more likely to be performed with MDT involvement (78.8% vs. 21.3%, p < 0.05). Comparing patients who received and did not receive MDT care, the mean HbA1c (%) (8.4 ± 2.0 vs. 8.2 ± 2.7, P = 0.701), median length of stay (LOS: 7.8, IQR 15.0 days vs. 4.8 IQR 7.9 days, P = 0.243) and rate of surgical outcomes (74.6% vs. 72.7%, P = 0.262) were similar. Patients who required major amputation had significantly longer LOS (24 days, IQR 21.5 vs. 5.2 days, IQR 13.0, P = 0.004) but similar HbA1c (P = 0.552) compared to those who had conservative intervention. Conclusion Adopting an MDT approach was associated with more thorough investigation of DFI, with similar rates of surgical outcomes. Further research on the impacts of MDT on length of stay and surgical outcomes of DFI patients in other SWS hospitals is needed.